Diagnostic performance of digital and traditional stethoscopes for detecting pneumonia-associated crackles in pediatric pneumonia patients - Udin, Muchammad Fahrul; Olivianto, Ery; Yusuf, Muhammad; Lestari, Hotma; Amar, Nasim; Bulain, Stanley; Raziq, Muhammad Abdul; Sajidah, Farah; Pareira, Raymundus Florentino Mariano; Anggarkusuma, Michelle Vanessa; Mulia, Rizki Hari (Paediatrica Indonesiana, 2025)
Background Advancements in healthcare technology have enabled the development of digital stethoscopes, enhancing auscultation in telemedicine practices. By remotely capturing and transmitting respiratory sounds, these devices improve physical examinations as well as the diagnosis and monitoring of respiratory diseases, particularly in remote or underserved areas. Objective To evaluate the sensitivity and specificity of a piezoelectric sensor-based digital stethoscope compared to a conventional stethoscope in detecting crackles associated with pediatric pneumonia. Methods This prospective comparative study involved 30 randomly selected pediatric pneumonia patients. Two pediatric pulmonologists independently assessed breath sounds in six lung areas using both digital and conventional stethoscopes. Findings were compared to evaluate the digital stethoscope’s sensitivity and specificity in detecting crackles, with the conventional stethoscope serving as the reference standard. Results The digital stethoscope demonstrated high sensitivity (>90%) and specificity (>90%) in detecting crackles, comparable to the conventional stethoscope. Examiner 1 achieved a sensitivity of 93.16%, a specificity of 97.10%, and an accuracy of 94.62%, while Examiner 2 achieved a sensitivity of 90.43%, a specificity of 91.55%, and an accuracy of 90.86%. The study highlights the potential of digital stethoscopes in telemedicine applications, particularly for pediatric respiratory assessments. Conclusion The digital stethoscope shows good diagnostic performance and may be a viable tool for remote auscultation. Its use may improve access to diagnostics in underserved areas or when in-person exams are difficult.